Comparison of the adjuvant effect of conbercept intravitreal injection at different times before vitrectomy for proliferative diabetic retinopathy - Yang, Zhikun; Di, Yu; Ye, Junjie; Yu, Weihong; Guo, Zijian (Frontiers in Endocrinology, 2023)
Purpose To assess the optimal time of intravitreal conbercept (IVC) treatment prior to pars plana vitrectomy (PPV) in patients with severe proliferative diabetic retinopathy (PDR). Method This study was exploratory in nature. Forty-eight consecutive patients (48 eyes) with PDR were divided into four groups according to different IVC times (0.5 mg/0.05 mL) before PPV: group A (3 days), group B (7 days), group C (14 days), and group D (non-IVC). Intraoperative and postoperative effectiveness were assessed, and vitreous VEGF concentrations were detected. Result For intraoperative effectiveness, groups A and D had a higher incidence of intraoperative bleeding than groups B and C (P = 0.041). Furthermore, groups A-C required less surgical time than group D (P < 0.05). For postoperative effectiveness, group B had a significantly higher proportion of visual acuity that improved or remained unchanged than group D (P = 0.014), and groups A-C had lower proportions of postoperative bleeding than group D. The vitreous VEGF concentration of group B (67.04 ± 47.24 pg/mL) was significantly lower than that of group D (178.29 ± 110.50 pg/mL) (P = 0.005). Conclusion IVC treatment that was administered 7 days preoperatively was associated with better effectiveness and a lower vitreous VEGF concentration than its administration at other time points.